Interleukin‐6 Trans‐Signaling Exacerbates Inflammation and Renal Pathology in Lupus‐Prone Mice. Issue 10 (24th September 2013) - Tsantikos, Evelyn; Maxwell, Mhairi J.; Putoczki, Tracy; Ernst, Matthias; Rose‐John, Stefan; Tarlinton, David M.; Hibbs, Margaret L.
<x xml:space="preserve">Abstract</x> Objective Systemic lupus erythematosus (SLE) is a heterogeneous autoimmune disease that is characterized by the production of antinuclear antibodies (ANAs) and leads to immune complex deposition in the kidneys and nephritis. Lyn tyrosine kinase is a regulator of antibody‐mediated autoimmune disease, as evidenced by studies in gene‐targeted mice and as suggested in genome‐wide association studies in SLE. Like SLE patients, Lyn‐deficient mice have increased levels of interleukin‐6 (IL‐6). Deletion of IL‐6 from Lyn‐deficient mice abrogates levels of inflammation, pathogenic autoantibodies, and nephritis. The purpose of this study was to assess the role of IL‐6 trans‐signaling in autoimmune disease by overexpressing soluble gp130Fc (sgp130Fc) in a mouse model. Methods The effect of overexpression of sgp130Fc on immune cell phenotypes was determined by flow cytometry in young and aged mice with lupus, and ANAs were measured by enzyme‐linked immunosorbent assay. Glomerulonephritis was assessed by histopathologic analysis, by measuring the glomerular area and the blood urea nitrogen concentration, and by immunohistochemistry. Immunofluorescence defined renal immune complex and complement deposition. The acute‐phase response was determined by quantitative real‐time polymerase chain reaction. Results In contrast to removing IL‐6, impaired IL‐6 trans‐signaling had little effect on many immune cell abnormalities in Lyn−/− mice. Pathogenic ANAs and kidney deposition of immune complexes were also unaltered by sgp130Fc. However, sgp130Fc overexpression led to diminished macrophage expansion, reduced glomerular leukocyte infiltration, reduced complement fixation, significantly attenuated glomerulonephritis, and improved renal function in Lyn‐deficient mice. Conclusion Our results reveal key roles of leukocytes, complement, and the innate immune system in mediating glomerulonephritis, and they implicate IL‐6 trans‐signaling in this process. We suggest that targeting this pathway may be an effective adjunct to B cell depletion in SLE treatment.